Macroscopic morphology of the male genitalia of Caenolestes caniventer (Caenolestidae: Paucituberculata) - Brito, Jorge; Nivelo-Villavicencio, Carlos; Reyes-Puig, Carolina; Yánez-Muñoz, Mario H. (Therya Notes, 2022)
The anatomy of the penis in the Paucituberculata has received little attention. The only treatise addressing the genitalia and prostate in this group of marsupials comes from a century ago. The present work describes the macroscopic morphology of the male genitalia of the gray-bellied shrew opossum, Caenolestes caniventer, a structure that can be useful in the taxonomic, reproductive, and evolutionary fields. The genitals were removed (n = 2) through a basal incision during the taxidermy of specimens and preserved in a 90 % alcohol solution. In the laboratory, genitals were prepared following eversion protocols and stained to highlight the structures. The penis and its structures were described. The penis has a long-wide glans with two distinctive prongs at distal end. A medium spermatic groove extends to the prongs. The prongs are 1.6 times longer than the glans, relatively cylindrical and striated, progressively tapering to a hook-shaped distal tip. Prong length and penile spines may be key to reproductive efficiency. We hypothesize that the family Caenolestidae generally displays similar penis shapes, with differences between species. These results are useful in taxonomic, reproductive, and evolutionary fields.